ANALISIS EFISIENSI DAN EFEKTIVITAS PENGELOLAAN KEUANGAN DAERAH - Osi Hayuni Putri (Al Fiddhoh: Journal of Banking, Insurance, and Finance, 2022)
This study aims to determine: level of efficiency and effectiveness in the financial management. The object of this research is Tanjung Jabung Timur Regency with a range of research years, namely 2010-2020. The analytical tool used is the formula Efficiency and Effectiveness. Based on the results of the study show that: The ability of the government of Tanjung Jabung Timur Regency in 2010-2020 is still less efficient, it is seen from the average level of efficiency in the management of regional finances which shows 97.01% results with the criteria of Not Efficient. From the results of the effectiveness analysis shows that the average value of the effectiveness of the level of financial management in Tanjung Jabung Timur Regency in 2010-2020 is 92.49%,which is asufficiently effective criteria.